Native Chicken Production in Indonesia: A Review - C. Hidayat; S. A. Asmarasari (Universitas Andalas, 2015)
Indonesia is a country rich in native chicken genetic resources. There are 31 native chicken breed in Indonesia. Native chicken farming was developed for decades. In early period of 1907’s, mostly farmers reared their native chicken by traditional system (about 80%). In 1980s until now, the number of native chicken farmers which rear native chicken by semi intensive and intensive system have been increasing. These rearing system changing have significantly increased the native chicken productivity. The major constraints for the development of native chicken i.e. low growth rate, risks of high mortality, low egg production. Many research results stated that improving in breeding, feeding and management aspect will increase native chicken production. The information and data contained in this paper is the result of study literature for scientific papers, either in the form of journals, books, or proceedings, and livestock statistics books. This paper is made to support the development of native chickens in Indonesia.